2017
DOI: 10.3892/ijo.2017.4113
|View full text |Cite
|
Sign up to set email alerts
|

Anoctamin5 regulates cell migration and invasion in thyroid cancer

Abstract: Anoctamin/TMEM16 family members have recently been identified as novel calcium-activated chloride channels, and dysregulation of many family members participates in tumorigenesis and progression. However, the exact role of anoctamin5 (ANO5), one member of this family, in thyroid cancer is still not clarified. In this study, we firstly found that the expression levels of ANO5 was significantly downregulated in thyroid cancer compared to adjacent normal tissue by mining the public GEO database. Subsequently, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 37 publications
(31 reference statements)
0
25
0
Order By: Relevance
“…Further, the expression of several members of the anoctamin family, such as ANO1, ANO5, ANO7, and ANO9, is correlated with the development of malignant tumors. Expression of ANO5 is downregulated in thyroid cancer, and knockdown of ANO5 promotes cell migration and invasion via regulation of the JAK/STAT3 signaling pathway . However, the exact role of ANO5 in prostate cancer has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the expression of several members of the anoctamin family, such as ANO1, ANO5, ANO7, and ANO9, is correlated with the development of malignant tumors. Expression of ANO5 is downregulated in thyroid cancer, and knockdown of ANO5 promotes cell migration and invasion via regulation of the JAK/STAT3 signaling pathway . However, the exact role of ANO5 in prostate cancer has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of ANO5 is downregulated in thyroid cancer, and knockdown of ANO5 promotes cell migration and invasion via regulation of the JAK/STAT3 signaling pathway. 25 However, the exact role of ANO5 in prostate cancer has yet to be determined. The position of rs4622263 overlaps with a GATA binding protein 1-bound region and is predicted to alter the regulatory motif transcription factor CP2-like 1, which has been implicated in maintenance of pluripotency and self-renewal in embryonic stem cells and cancers, 28,29 according to the experimental chromatin immunoprecipitation sequencing data in the HaploReg database.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no significant decrease in HER2 transcription by this treatment was noted in YMB‐1 cells (Figure C). Chang et al showed that inhibition of ANO5 activated the JAK/STAT3 signaling pathway in thyroid cancer cells. High ANO1 activity in YMB‐1 cells may prevent the constitutive JAK/STAT3 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…TMEM91 encodes a protein belonging to the transmembrane protein family which mediates a number of human physiological processes, such as the regulation of cell migration and invasion, constructs ion channels, and participates in the immune response [ 29 31 ]. At present, research on the TMEM family members focuses mostly on the field of cancer; however, their relationship with thyroid disease is unknown [ 32 ].…”
Section: Discussionmentioning
confidence: 99%